2014
DOI: 10.1007/s11192-014-1461-x
|View full text |Cite
|
Sign up to set email alerts
|

Careers of young Polish chemists

Abstract: Typical young Polish scientist is an alumnus of doctoral studies at the same university and department where he/she completed his/her Master degree. The career is continued by receiving a habilitation at the same university and department. Then a holder of habilitation is promoted to a tenured position at the same university and department. Detailed analysis of scientific careers of 154 recent Ph.D. recipients and of 16 habilitation candidates in chemistry from University of Warsaw is presented. More than 96 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 8 publications
0
8
0
2
Order By: Relevance
“…However, the outlook on policies to curtail academic inbreeding was remarkably similar between the Russian and Portuguese experts. There was a complete aversion to the idea of terminating academic inbreeding by decree, which was understood as potentially more detrimental than beneficial (terminating academic inbreeding by decree is also problematic, as the decree regulations to prevent this practice can always be circumvented; see Kosmulski, 2014 regarding the case of Poland). Instead, it was suggested that policies strongly supporting internationalization and brain-circulation could be critical in changing mentalities and in promoting the integration and dissemination of novel ideas (Heitor et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…However, the outlook on policies to curtail academic inbreeding was remarkably similar between the Russian and Portuguese experts. There was a complete aversion to the idea of terminating academic inbreeding by decree, which was understood as potentially more detrimental than beneficial (terminating academic inbreeding by decree is also problematic, as the decree regulations to prevent this practice can always be circumvented; see Kosmulski, 2014 regarding the case of Poland). Instead, it was suggested that policies strongly supporting internationalization and brain-circulation could be critical in changing mentalities and in promoting the integration and dissemination of novel ideas (Heitor et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…It consolidates power structures benefiting often senior academics, thus providing a powerful incentive for the practice to be maintained (Godechot & Louvet, 2008), and becomes understood as part of the 'normal' academic life (Altbach et al, 2015). Legal drastic measures to curtail the practice have been enforced in some countries, with varied degrees of success (Kosmulski, 2015), but the main challenge has been one of changing institutional cultures, and public policies promoting change of mentalities and behaviours through national and international mobility schemes have been suggested as a strategy that may take longer but be more effective (Horta & Yudkevich, 2016;Tavares et al, 2019).…”
Section: Liter Ature Re Vie Wmentioning
confidence: 99%
“…Consequently, they may find themselves having to move around different institutions to 'get ahead'. Inherently mobile, they are unlikely to amass the prestige and valued capital required when compared to their relatively immobile guild-route counterparts, which may play a not insignificant part in the prevalence of academic inbreeding among the 'top', elite institutions (Altbach et al, 2015;Horta et al, 2010) in many nations, including Argentina (Rabossi, 2015), Poland (Kosmulski, 2015) and Spain (Cruz-Castro & Sanz-Menéndez, 2010;Rocca, 2007). Bourdieu's (1977) concept of the habitus provides a way to analyse the social world and social practices, to explore the effect of this 'guild' membership in academe.…”
Section: Inhab Iting the ' Ri G Ht ' Hab Itusmentioning
confidence: 99%